Association between PRKAA1 rs13361707 T>C polymorphism and gastric cancer risk: Evidence based on a meta-analysis. Issue 14 (April 2018) - Jiang, You; Li, Wenbo; Lu, Jun; Zhao, Xin; Li, Liang
Abstract: Background: Recently, several published studies investigating the relationship between protein kinase catalytic subunit alpha-1 gene ( PRKAA1 ) rs13361707 T>C polymorphism and gastric cancer (GC) susceptibility reported controversial results. The purpose of this meta-analysis was to estimate the strength of the relationship. Methods: Qualified studies were identified form a comprehensive search conducted in the Embase, Pubmed, Wangfang, and China National Knowledge Infrastructure (CNKI) databases for studies published before February 12, 2018. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the relationship between the PRKAA1 rs13361707 T>C polymorphism and GC risk. Results: Fifteen independent case-control studies, which included 14, 615 GC patients and 18, 143 control subjects, were included in this present meta-analysis. The overall analysis of the 15 studies indicated that the PRKAA1 rs13361707 T>C polymorphism significantly increased susceptibility for GC in all genetic models. When stratified analysis was carried out by country and source of controls, similar results were found in each subgroup, except for the Hispanic Americans. There was no publication bias in our study. Omitting each study 1 at a time in the sensitivity analysis of the PRKAA1 rs13361707 T>C polymorphism and GC risk had no noticeable influence on the pooled OR, which identified the reliability of the meta-analysis. False-positive report probability analysis and trial sequential analysis demonstrated that such relationship was confirmed in the present study. Conclusions: The meta-analysis reveals that the PRKAA1 rs13361707 T>C polymorphism has a significant relationship with increased GC risk. To confirm the risk identified in the present meta-analysis, well-designed and large-scale case-control studies are warranted to investigate the relationship, especially among non-Asian ethnicity. Abstract : Supplemental Digital Content is available in the text